The potential of renewable energy to improve energy, food, and financial security at farm level in the Langeberg Local Municipality, South Africa - Abelheim, Jonathan (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.